Assessment of the usability of Tam Bo bentonite (Di Linh - Lam Dong) for peloid - Man, Tran Thi; Lan, Tran Thi; Duong, Nguyen Anh; Anh, Phan Luu (Vietnam Journal of Earth Sciences, 2020)
The study was carried out to assess the suitability of Tam Bo bentonite for application in peloid. By using the XRD analysis method, the results showed that the mineral component of Tam Bo bentonite was mainly smectite (montmorillonite) (55–73%), illite (10-14%), quartz (10–16%), and minor minerals such as siderite, feldspar, goethite, chlorite and kaolinite. Chemical composition of the samples analyzed by the XRF method composed of a high amount of SiO2 (51.38–55.16%) and Fe2O3 (5.31–7.97%), low content of Al2O3 (14.58–20.87%), and the other oxides with low content. The analysis result using the ICP-OES method indicated that bentonites in Tam Bo consisted of trace elements such as As, Ba, Cr, Cd, Co, Cu, La, La, Pb, Sb, Sc, V, Zn, and their content is similar to the values in peloid for the commercial use. Tam Bo bentonite has a pH value of 8.17, a very high CEC index (71 mg/100g), a plasticity index of 28%, expandability of 70%. All of the samples did not contain pathogenic bacteria. The study result confirms that Tam Bo bentonite responses to the criteria for making the peloid and similar to the peloids of Vale das Furnas (in Portugal), Calda (in Italy), Archena (in Spain).